The Co-Operative Principle and its Maxims as a Translation Tool - Mijas, Hanna (Respectus Philologicus, 2005)
The subject matter of the present article is an overview of H P. Grice’s theory of conversation, as formulated in his university publications, and its application in translation studies. The article focuses on implicature based on the Gricean Co-operative Principle and its maxims. The main objective is to show through various examples of translations from English into Polish that such a notion proves to be particularly useful in highlighting areas of difficulty in cross-cultural communication. What is more, it can successfully serve as a tool for the translator who is aware of the fact that any given text should not be considered as a static example of language but as a verbalised expression of the author’s intention, which in turn, needs to be understood and recreated by the translator for another reader in a different culture.
Keywords: pragmatics; implicature; Co-operative Principle; maxims; translation; translator